Challenges and Solutions in Implementing a Healthy Indonesia Program with a Family Approach - Sulistiowati, Eva; Leny Susyanty, Andy; Fajarwati, Tetra; Nur Sapardin, Aprildah; Dewi Susilawati, Made; Avrina, Rossa; Mujiati; Nur Hasanah, Siti; Sri Hartati, Nova; Dwi Harso, Agus; et al. (Media Kesehatan Masyarakat Indonesia, 2020)
The Healthy Indonesia Program with a Family Approach (PISPK) is conducted by puskesmas by integrating existing resources, with the family’s target. All families will get access to comprehensive health services. The implementation of PISPK since 2016 has not been optimal because it has many obstacles. The analysis aims to identify the obstacles, and to find solutions to implemented PISPK optimally. Implementation research was carried out using Participatory Action Research (PAR). The team (researcher and subject) implemented PISPK together based on stages that integrated into puskesmas management, at 4 puskesmas in South Lampung. Researchers assisted and recorded data collected qualitatively (self- assessment, in-depth interviews, Focus Group Discussion), and quantitatively. There are any obstacles occurred in the implementation of PISPK such as the absence of regulations and cross-sectoral supports; lack of knowledge and support from village officials, community leaders, and the public; limited resources; lack of understanding of the substantive; application; lack of data analysis capabilities. These obstac-les can be minimized by making some breakthroughs, such as advocacy and issuance of local government regulations on PISPK involving cross-sectors; increase socialization; periodic coordination, monitoring, and evaluation; making innovations (On Job Training, collaboration with universities and health volunteer, Healthy Family Coverage Pocket Book, developing data analysis methods). The implementation of PISPK has many obstacles that can be minimized by optimizing existing potentials and support from stakeholders. Puskesmas need to increase socialization; team organizing; data analysis; coordination, and routine monitoring evaluation. Pusdatin needs to improve KS applications to be more user-friendly.